Act of May 5, 1777, ch. 3, in 9 HENING'S STATUTES AT LARGE 281, 281-82 (1821) - (:unkn) unknown (My University, 1777)
An act to oblige the free male inhabitants of this state above a certain age to give assurance of Allegiance to the same, and for other purposes. WHEREAS allegiance and protection are reciprocal, and those who will not bear the former are not entitled to the benefits of the later, Therefore Be it enacted by the General Assembly, that all free born male inhabitants of this state, above the age of sixteen years, except imported servants during the time of their service, shall, on or before the tenth day of October next, take and subscribe the following oath or affirmation before some one of the justices of the peace of the county, city, or borough, where they shall respectively inhabit; and the said justice shall give a certificate thereof to every such person, and the said oath or affirmation shall be as followeth, viz . . . And the justices tendering such oath or affirmation are hereby directed to deliver a list of the names of such recusants to the county lieutenant, or chief commanding officer of the militia, who is hereby authorised and directed forthwith to cause such recusants to be disarmed
Keywords: ARMED FORCES